2011
DOI: 10.1007/s12665-011-1219-1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of an integrated water resource management for the Distrito Federal, Western Central Brazil: climate, land-use and water resources

Abstract: Land-use/cover change (LUCC) and climate change are major controlling factors for water resources in the Distrito Federal in Western Central Brazil. Dynamic LUCC in the region has severe impacts on water resources, while climate changes during the last three decades is thought to have only moderate effects. LUCC affects water quantity mostly during base flow conditions. River basins with substantial expansion of agriculture since the end 1970s show a dramatic decrease of base flow discharge by 40-70%, presumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 40 publications
0
30
0
4
Order By: Relevance
“…[7][8][9][10] However, our data support that WWTP may be an important source of emerging contaminants if diffuse inputs and water circulation are considered. The latter aspect was also investigated by Goldscheider et al 32 in Geneva Lake (Switzerland) where contaminant transport does not occur by homogeneous mixing processes, but in the form of plumes with sharp boundaries, being not possible to draw an iso-concentration line between the measured concentrations.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…[7][8][9][10] However, our data support that WWTP may be an important source of emerging contaminants if diffuse inputs and water circulation are considered. The latter aspect was also investigated by Goldscheider et al 32 in Geneva Lake (Switzerland) where contaminant transport does not occur by homogeneous mixing processes, but in the form of plumes with sharp boundaries, being not possible to draw an iso-concentration line between the measured concentrations.…”
Section: Resultsmentioning
confidence: 74%
“…Our results show that in this portion of the lake, caffeine concentration was higher in the sampling point immediately after the WWTP (PL3) and diminished at the subsequent sampling point (PL4) indicating a possible dilution and/or degradation. Lorz et al 7 showed that the concentration of organic micropollutants in Paranoá Lake decreases significantly as the distance to WWTPs becomes higher, probably due to the fast and efficient degradation processes triggered by high water temperatures and permanent UV irradiation. However, their conclusions were based on data collected from sampling points situated in different locations of the lake, i.e., one in each of the four branches and another nearby the dam at the eastside portion of the lake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O adensamento populacional no Distrito Federal tem provocado importantes mudanças ambientais (LORZ et al, 2012). No Distrito Federal houve um processo desorganizado da ocupação do território por condomínios privados, onde muitos são irregulares ou ilegais ocupando áreas de preservação permanentes, como: nascentes, faixa marginal de rios e encostas de morros (PAVIANI, 2010).…”
Section: áRea De Estudounclassified
“…Urbanization and intense activities of urban population as well as substantial expansion of agriculture areas and cattle are identified as the major causes of environmental problems in Brazil, including pollution of water resources (Tucci 2008;Lorz et al 2012;Da Silva et al 2013). The Pardo River is an important water body, which is being considered as a future water supply.…”
Section: Introductionmentioning
confidence: 99%